External evaluation of the students of sixth primary course in the province of Teruel - school year 2012/13 - José Luis Castán Esteban (ADIDE Federación, 2014)
This paper analyzes the development process and findings of the external test linguistic and mathematical competence in May 2013 to all sixth grade students of Primary Education of the Province of Teruel. It was performed according to the methodology of international assessments (Pirls, Timss, Pisa). The test was coordinated by the Education Inspectorate and has been a landmark, both for information on the results of the students by the inspection and teachers to implement improvement plans in schools.